Explaining social exchanges in Information-Based Online Communities (IBOCs). Issue 4 (15th August 2016) - Benoit, Sabine; Bilstein, Nicola; Hogreve, Jens; Sichtmann, Christina
Abstract : Purpose: Information-based online communities (IBOCs, like LinkedIn or Facebook) provide platforms for members to exchange information. Because member participation is vital for IBOCs, this research aims to identify and validate factors that drive member participation. Design/methodology/approach: With reference to social exchange theory we developed a model of antecedents of participation in IBOCs that was tested with survey data using PLS. Because some of our results contradicted the theory, we examined those results in a mainly qualitative study with online community providers. These experts offered explanations that inform our discussion and managerial implications. Findings: Role clarity, provider's responsiveness, and enjoyment all influence member participation. Contrary to theory, the cooperation of other members affects member participation negatively while a member's ability shows no effect. Practical implications: This research has several implications for IBOC providers. Because ability does not affect participation directly, providers do not need to worry about lacking ability and can effectively target all potential members. The importance of provider responsiveness signals that IBOC providers should proactively monitor members' compliance with social norms to lower the social risk for members. The impact of community specific knowledge and enjoyment on participation puts emphasis on careful community design and the thoughtful implementation of new features that might enhance enjoyment, but reduce role clarity. Originality/value: Whereas most of the participation literature focuses on a dyadic relationship, our research investigates the triadic relationship in which the provider is only an enabler of exchange. Furthermore, we bring together two streams of the literature: the participation literature, which tends to focus on offline participation; and the online community literature, which has not yet investigated participation. This is also the first paper to investigate nonlinear effects on participation.